Simulating seasonal variations of tile drainage discharge in an agricultural catchment. Issue 5 (13th May 2017) - De Schepper, G.; Therrien, R.; Refsgaard, J. C.; He, X.; Kjaergaard, C.; Iversen, B. V.
Abstract: Seasonal variations of tile drainage discharge were simulated in the 6 km 2 Fensholt catchment, Denmark, with the coupled surface and subsurface HydroGeoSphere model. The catchment subsurface is represented in the model by 3 m of topsoil and clay, underlain by a heterogeneous distribution of sand and clay units. Two subsurface drainage networks were represented as nodal sinks. The spatial distribution of the heterogeneous units was generated stochastically and their hydraulic properties were calibrated to reproduce drainage discharge for one network and verified with drainage discharge for the other network. Simulated discharge was compared to that of another model for which the heterogeneous sand and clay units were replaced by a homogeneous unit, whose hydraulic conductivity was the mean value of the heterogeneous model. With the homogeneous model, drainage dynamics were correctly simulated but drainage discharge was less accurate compared to the heterogeneous model. Simulated discharge was also compared to that of a larger‐scale model created with the MIKE SHE code, built with the same heterogeneous model. HydroGeoSphere and MIKE SHE generated drainage discharge that was significantly different, with better simulated groundwater dynamics data produced by HydroGeoSphere. Nodal sinks in HydroGeoSphere reproduced drain flow peaks more accurately. Calibration against drainage discharge data suggests that drain flow is controlled primarily by geological heterogeneities included in the model and, to a lesser extent, by the nature of the soil units located between the drains and ground surface. Plain Language Summary: In temperate regions, climate conditions may cause groundwater levels to be at or very close to the land surface, resulting in reduced crop yields. Therefore, a substantial part of agricultural lands is drained by subsurface pipes. While measuring drainage discharge is easy, identifying the origin of drainage water is complicated. This is where computer models are useful. Models allow for representing the underground of a selected region in numerical replicas. By building such replicas, we can virtually observe water flowing in the underground and at the land surface. Understanding the effect of drainage on water flow is essential to choose appropriate management techniques regarding fertilizer application by farmers for example. Yet reproducing drainage water flow with models is a challenge. In our case, we chose to build a replica of the Fensholt agricultural area in Denmark. Drainage outflow from two agricultural fields showed that the structure of the shallow underground, which is not thoroughly known, controls drainage outflow. This suggests that improving the underground knowledge is crucial to set effective farming strategies. Key Points: We develop a 3‐D coupled surface‐subsurface hydrological catchment scale model focusing on local scale tile drainage Multiyear seasonal drainage variations were simulated and adequately reproduced Calibrated results suggest that shallow porous media properties control drain flow